Peningkatan Pemahaman Membaca Awal Menggunakan Media Huruf Balok Siswa Disabilitas Intelektual Ringan (Single Subject Research di Kelas III/C SLB Perwari Padang) - Riri Riri Puspita Sari; Armaini Armaini (Jurnal Penelitian Pendidikan Khusus, 2023)
Reading is a basic ability possessed by children which includes physical and mental. Reading comprehension is a skill and cognitive activity. Improving early reading comprehension for students with mild intellectual disabilities is not through an easy way, because these students with mild intellectual disabilities have IQs that do not reach the average, therefore educators must act calmly and the learning tools used by educators are also interesting and fun so that students with disabilities intellectually unsaturated and understanding during learning activities. Therefore, the problem that will be studied in this study is "how can the use of block letters improve early reading comprehension for students with mild intellectual disabilities?"Type of study examines the assessment through a single subject or single subject research (SSR), the design is A-B-A. This study was carried out using letter tools as detachment factors, and early reading ability factors. This study uses in-state and inter-state analysis which can be proven at a stable skew when measuring A1 is equal to 0%. Then the occurrence of additional time given the treatment (B) which measures the result equal to 49% and before being given treatment is the state of A2 measuring the result equal to 72%. So it can be summarized that the improvement in each situation is that students are able to recognize letters that are read backwards.